A Review on Ficus Religiosa Moraceae: Distribution, Traditional Uses and Pharmacological Properties - Kumari, Kamini; Jangir, Surbhi; Prajaptai, Virendra; Ram Ratan; Sonali Rastogi; Prajapati, V.M.; Shrivastava, Sargam; Tater, Ritika (Journal of Biomedical and Pharmaceutical Research, 2022)
Medicinal plants play a vital role in improving the health of people. Hundreds of medicinal plants have been used to cure various diseases since ancient times. Ficus religiosa (Peepal) has an important place among herbal plants. Almost every part of this tree i.e., leaves, bark, seeds, and fruits are used in the preparation of herbal medicines. Ficus religiosa is grown by specialty tree plant nurseries for use as an ornamental tree, in gardens and parks in tropical and subtropical climates. Peepul trees are native to Indian subcontinent and thrive in hot, humid weather. They prefer full sunlight and can grow in all soil types, though loam is the best. When planting, use soil with a pH of 7 or below. It is native to the Asia-Tropical (Bangladesh; India, Nepal, Pakistan, China, Myanmar, Thailand, Vietnam, and Iraq) and it is cultivated in wide tropical areas. Peepal is a large, fast-growing deciduous tree. It has a heart-shaped leaf. It is a medium size tree and has a large crown with wonderful wide-spreading branches. The fruits of the Peepal are hidden with the figs. It has fast-growing nature, tolerance to various climate zones and soil types, reported lifespan of over 3,000 years, and its suffocating growth habit as it often begins life as an epiphyte. Different parts of plants have been used in the Indian traditional system of medicine such as: Anti-diabetic, Anti-inflammatory, Antioxidant, Analgesic, Anticonvulsant, Antimicrobial, Wound healing, Anti-amnesic, Anti-fertility, Anti-ulcer, Anti-Parkinson, Anti-asthmatic, Kidney-protective, Toothache and Eye ache.